Diagnostický postup u těhotenství nejisté viability a neznámé lokalizace - nejnovější doporučení - Fischerová, D; Frühauf, F; Břešťáková, L (Ceska gynekologie, 2014)
Based on current knowledge the criteria for diagnosing nonviability in early intrauterine pregnancy and diagnostic algorithm in pregnancies of unknown location have changed. For either an intrauterine pregnancy of uncertain viability or a pregnancy of unknown location, the consequences of false positive diagnosis of nonviability or false negative diagnosis of ectopic pregnancy may be dire: harming of a potentially normal intrauterine pregnancy or a life-threatening rupture from tubal pregnancy. This review aims to present the most important results of current studies on this topic with their recommendations and to improve patient care reducing the risk of inadvertent harm to potentially normal pregnancies.
Keywords: ženské pohlaví; těhotenství; Female; mimoděložní těhotenství; směrnice pro lékařskou praxi jako téma; algoritmy; Diagnostic Techniques, Obstetrical and Gynecological; lidé; Practice Guidelines as Topic; Algorithms; diagnostické techniky porodnicko-gynekologické; Pregnancy, Ectopic; Humans; Pregnancy